BREAST CANCER RISK PREDICTION USING DATA MINING CLASSIFICATION TECHNIQUES - Williams, Kehinde; Idowu, Peter Adebayo; Balogun, Jeremiah Ademola; Oluwaranti, Adeniran Ishola (Discoveries in Agriculture and Food Sciences, 2015)
Breast cancer poses serious threat to the lives of people and it is the second leading cause of death in women today and the most common cancer in women in developing countries in Nigeria where there are no services in place to aid the early detection of breast cancer in Nigerian women. A number of studies have been undertaken in order to understand the prediction of breast cancer risks using data mining techniques. Hence, this study is focused at using two data mining techniques to predict breast cancer risks in Nigerian patients using the naïve bayes’ and the J48 decision trees algorithms. The performance of both classification techniques was evaluated in order to determine the most efficient and effective model. The J48 decision trees showed a higher accuracy with lower error rates compared to that of the naïve bayes’ method while the evaluation criteria proved the J48 decision trees to be a more effective and efficient classification techniques for the prediction of breast cancer risks among patients of the study location.